Psychiatric comorbidity and traumatic brain injury attribution in patients with psychogenic nonepileptic or epileptic seizures: A multicenter study of US veterans. (24th August 2018) - Salinsky, Martin; Rutecki, Paul; Parko, Karen; Goy, Elizabeth; Storzbach, Daniel; O'Neil, Maya; Binder, Laurence; Joos, Sandra
Summary: Objective: To determine the frequency and severity of psychiatric disorders and attribution of seizures to traumatic brain injury (TBI) in veterans with verified psychogenic nonepileptic seizures (PNES) versus epileptic seizures (ES). Methods: We studied 333 consecutive admissions to the monitoring units of three Veterans Administration epilepsy centers. All patients underwent continuous video‐electroencephalographic recording to define definite PNES or ES. Evaluations included the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, 4th edition, PTSD Checklist, Beck Depression Inventory II, and Patient Seizure Etiology Questionnaire. Interviews and questionnaires were completed prior to final seizure type diagnosis and patient debriefing. The primary outcome measure was a comparison of Axis I psychiatric diagnoses in patients diagnosed with PNES versus ES. Results: A total of 81 patients were diagnosed with PNES, and 70 with ES. PTSD was the most frequent Axis I diagnosis in veterans with PNES (64%, vs 13% of those with ES; P < 0.001). Posttraumatic stress disorder (PTSD) was common regardless of deployment to a war theater or combat exposure. Mood, substance abuse, and anxiety disorders were also more common in the PNES group. TBI was cited as a likely cause of seizures by 47% of veterans with PNES versus 25% of those with ES ( P = 0.01). PTSD and attribution of seizures to TBI were found in 30% of veterans with PNES versus 3% of those with ES ( P < 0.001). Significance: In veterans referred for inpatient seizure evaluation, PTSD was strongly associated with a diagnosis of PNES versus ES. The association of PNES with PTSD, attribution of seizures to TBI, or both, may prompt early consideration of PNES.